Indicators of Coastal Wetlands Restoration Success: A Systematic Review - Cadier, Charles; Bayraktarov, Elisa; Piccolo, Renee; Adame, Maria Fernanda (Frontiers in Marine Science, 2020)
Coastal wetlands restoration is an emerging field which aims to recover their ecological characteristics of degraded ecosystems to natural ones. The recent UN declaration of 2021-2030 being the “Decade on Ecosystem Restoration” will hopefully encourage global implementation of these projects. However, a lack of common indicators of restoration success hinders our knowledge on the ecological outcomes of restoration projects. We conducted a literature review to determine trends in monitoring indicators. We classified indicators following the Society for Ecological Restoration template, adapting it to coastal wetlands. We found that indicators on structural diversity (e.g. tree height, fish size) were the mostly commonly used. Indicators on ecosystem function was the second most investigated, with half of the assessment studies including them, especially those focusing on carbon, nutrient and sediment dynamics. We propose a recovery wheel framework adapted to coastal wetlands. Structural diversity indicators are generally easier to measure and often the fastest to recover. However, ecosystem functions indicators could be more important to assess the recovery of ecosystem services, which is a primary objective of restoration. Restoration objectives and goals are variable for each project, and we encourage future restoration projects on coastal wetlands to select the most appropriate indicators on the basis of the recovery wheel proposed in this study to plan their monitoring framework. Future studies assessing coastal wetlands restoration ecological outcomes should include ecosystem function indicators and monitor the sites over time period adequate to their recovery.